Eroding Sovereignty and Culture: The Impact of The Doctrine of Discovery on Onondaga Sovereignty and Cultural Integrity - Chavez, Samantha (The Toro Historical Review, 2025)
This research paper examines the enduring impact of the Doctrine of Discovery on Native American sovereignty, with a focus on the Onondaga Nation and the Iroquois Confederacy. By tracing the doctrine's legal, political, and cultural consequences, it is revealed how the Doctrine and its language has been used to justify the dispossession of Native lands while contributing to the erosion of Indigenous self-governance. This paper looks directly at the Onondaga Nation whom have actively fought against the consequences of the Doctrine to assert their sovereignty. Drawing on treaties, legal documents, and case rulings this project highlights the intersection of colonial ideologies and Native resilience, advocating for a critical reevaluation of historical injustices and their contemporary implications.